Correlates of quality of life and mental health among youth experiencing homelessness in Iran - Neda Malekmohammadi; Soheil Mehmandoost; Mehrdad Khezri; Hossein Mirzaei; Fatemeh Tavakoli; Ghazal Mousavian; Mansureh Safizadeh; Abedin Iranpour; Hamid Sharifi (BMC Psychology, 2023)
Abstract Background Quality of life (QOL) and mental health among marginalized populations, including people experiencing homelessness in Iran, are understudied. We assessed the QOL and mental health status as well as their associated factors among youth experiencing homelessness in Kerman, Iran. Method We recruited 202 participants using a convenience sampling method from 11 locations, including six homeless shelters, three street outreach sites, and two drop-in service centers, from September to December 2017. Data were collected using a standardized questionnaire that included QOL, mental health, demographics, drug use, and sexual behaviors questions. Scores in each domain were indexed with a weight of 0-100. The higher score indicated a higher QOL and mental health status. Bivariable and multivariable linear regression models were performed to examine correlates of QOL and mental health. Result The mean (SD) score of QOL and mental health were 73.1 (25.8) and 65.1 (22.3), respectively. Multivariable analysis showed that youth experiencing homelessness who were aged 25–29 years old (β = -5.4; 95% CI: -10.51; -0.30), and lived on the streets (β = -12.1; 95% CI: -18.19; -6.07) had a lower mental health score. Moreover, those who had higher education (β = 5.4; 95% CI: 0.58; 10.38), had no history of carrying weapons (β = 12.8; 95% CI: 6.86; 18.76), and had a higher QOL score (β = 0.41; 95% CI: 0.31; 0.50) had a higher mental health score. Conclusion This study highlights that QOL and mental health among youth experiencing homelessness in Iran are concerning, particularly among those who were older, were less educated, were living on the street, and had a history of carrying a weapon. Community-based programs, including mental health care and affordable housing are needed to improve QOL and mental health among this population in Iran.